Cost-effectiveness of Triple Therapy with Telaprevir for Chronic Hepatitis C Virus Patients in Germany - Jona T. Stahmeyer; Svenja Schauer; Siegbert Rossol; Hans Heinrich Wedemeyer; Daniel Wirth; Florence Bianic; Christian Krauth (Journal of Health Economics and Outcomes Research)
# Background About 400,000-500,000 people are infected with hepatitis C in Germany. Long-term consequences are the development of liver cirrhosis and hepatocellular carcinoma. The introduction of first generation protease inhibitors has significantly improved the treatment of hepatitis C genotype 1 patients. The aim of the study was to assess the cost-effectiveness of triple therapy with telaprevir in Germany.